Lack of gene–diuretic interactions on the risk of incident gout: the Nurses' Health Study and Health Professionals Follow-up Study. Issue 7 (9th February 2015) - Bao, Ying; Curhan, Gary; Merriman, Tony; Plenge, Robert; Kraft, Peter; Choi, Hyon K
Abstract : Background: Diuretic-induced gout might occur only among those with a genetic predisposition to hyperuricaemia, as suggested by a recent study with 108 self-reported gout cases. Methods: We examined the role of urate genes on the risk of diuretic-induced incident gout in 6850 women from the Nurses' Health Study (NHS) and in 4223 men from the Health Professionals Follow-up Study (HPFS). Two published genetic risk scores (GRSs) were calculated using urate-associated single-nucleotide polymorphisms for 8 (GRS8) and 29 genes (GRS29). Results: Our analyses included 727 and 354 confirmed incident gout cases in HPFS and NHS, respectively. The multivariate relative risk (RR) for diuretic use was 2.20 and 1.69 among those with GRS8 < and ≥ the median (p for interaction=0.27). The corresponding RRs using GRS29 were 2.19 and 1.88 (p for interaction=0.40). The lack of interaction persisted in NHS (all p values >0.20) and in our analyses limited to those with hypertension in both cohorts. SLC22A11 (OAT4) showed a significant interaction only among women but in the opposite direction to the recent study. Conclusions: In these large prospective studies, individuals with a genetic predisposition for hyperuricaemia are not at a higher risk of developing diuretic-induced gout than those without.